Pengaruh Gerak dan Lagu terhadap Kepercayaan Diri Anak Usia 5-6 Tahun di PAUD Mutiara Medan - Hilma Mithalia Shalihat; Niken Farida; Rahmi Wardah N.; Ester Diana Lahagu (Mathematics Education Study Program, 2025)
This research aims to determine The Influence of Songs and Movement on Children Self-Confidence Aged 5 - 6 Years at Mutiara Kindergarten Medan. The type of this research is experimental research with pre-experimental one group pretest and posttest design. Subjects of this research were 11 children in class B. Technique sampling used was total sampling. Data collection techniques used were observation and documentation. The data from this research were analyzed by using SPSS 25 statistics with the formula mean, median, mode, Shapiro-Wilk normality test, paired-children’ssample t-test. Based on the results of data analysis, it was found that children's confidence in the pretest obtained an average score of 7.45 with a percentage of 37%, while in the posttest it increased with an average score of 13.09 with a percentage of 65%. Based on the hypothesis test, the results of the paired sample t-test analysis show the results of t count < t table (18,204 < 2,262) and a significant value is 0.02 < 0.05, which means that Ho is rejected and Ha is accepted. So it can be concluded that there is an influence of the use of songs and movement on children self-confidence aged 5 - 6 years at Mutiara Kindergarten Medan.